2016
DOI: 10.1016/j.coal.2016.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Organic petrology and geochemistry of mudrocks from the lacustrine Lucaogou Formation, Santanghu Basin, northwest China: Application to lake basin evolution

Abstract: Exploration for tight oil in the frontier Santanghu Basin of northwest China has resulted in recent commercial discoveries sourced from the lacustrine Upper Permian Lucaogou Formation, already considered a "world class source rock" in the Junggar Basin to the west. Here we apply an integrated analytical program to carbonate-dominated mudrocks from the Lucaogou Formation in Santanghu Basin to document the nature of organic matter (OM) in the context of an evolving lake system. The organic-rich samples wt.%; n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…Kerogen with HI values >200mg HC/g TOC can generate oil, although the main products are typically both gas and condensate oil. HI values > 300 mg HC/g TOC are the generally accepted conditions for forming petroleum reservoirs (Hackley et al, 2016). Thus, it can be concluded that the samples are gas-prone source rocks based on the HI values (102-303 mg HC/g TOC).…”
Section: Hydrocarbon Generation Potential Of the Organic Mattermentioning
confidence: 91%
See 1 more Smart Citation
“…Kerogen with HI values >200mg HC/g TOC can generate oil, although the main products are typically both gas and condensate oil. HI values > 300 mg HC/g TOC are the generally accepted conditions for forming petroleum reservoirs (Hackley et al, 2016). Thus, it can be concluded that the samples are gas-prone source rocks based on the HI values (102-303 mg HC/g TOC).…”
Section: Hydrocarbon Generation Potential Of the Organic Mattermentioning
confidence: 91%
“…The distribution of R o is generally in the range from 0.59% to 0.83%. This indicates that the coal measure source rocks are within the oil window for hydrocarbon generation, since the thermal maturity varies with the type of organic matter between 0.5% and 1.0% for the oil window and from 1.3% to 3.5% for the gas window (Farhaduzzaman et al, 2013;Hackley et al, 2016). T max is also a reliable and useful indicator for thermal maturity since it is unaffected by weathering (Singh et al, 2010;Xie et al, 2016).…”
Section: Organic Matter Type and Thermal Maturitymentioning
confidence: 98%
“…Eagle Ford, Barnett and Marcellus of North America have proven reserves sourced from Neoproterozoic deeply buried unconventional 'tight' petroleum systems. These to a large extend according Energy Information Administration (2015), Hackley et al (2016) is responsible for USA being ranked as the leading world producer of oil and gas since 2013. These oil-shales in North America are characterized by solid oily bitumen as the main organic matter (Hackley et al 2016;Wang et al 2016).…”
Section: Global Neoproterozoic Petroleum Occurrencementioning
confidence: 99%
“…Santanghu Coalfield is located at Barkol County and Yiwu County, Northeast Xinjiang Province, with a strip shape oriented NW-SE between Moqinwula and Suhaitu Mountains (Liu et al 2012a, b;Song et al 2013;Ge et al 2015;Hackleya et al 2016). Santanghu Coalfield is the largest integrated Coalfield prospecting area in Xinjiang and even in China.…”
Section: Geological Settingmentioning
confidence: 99%